A SEMIOTIC STUDY IN ADVERTISEMENTS OF BEAR BRAND STERILIZED MILK “PREVENTING” AND “RECOVERING” VERSION - SAPHAN, SERRY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotics, Sign, Connotative Meaning, AdvertisementSemiotics is well known as the study of sign. This study aims to analyze the signs andthe meanings found in the advertisements of Bear Brand Sterilized Milk “preventing” and “recovering” version. There are two problems to be solved, namely: (1) What signs are found in advertisements of Bear brand Sterilized Milk “preventing” and “recovering” version?; (2) What meanings are found from the signs in advertisements of Bear Brand Sterilized Milk preventing” and “recovering” version?This study is a qualitative approach which is conducted though descriptive method.This study applies Peirce’s three modes of signs to investigate the signs employed in the advertisements. Barthes’ connotative meaning concept is applied in this study to analyze the meaning of the advertisements. The research design is document analysis since the data are the seven advertisements of Bear Brand Sterilized Milk “Preventing” and “Recovering” version. There are 17 (seventeen) advertisements of Bear Brand Sterilized Milk and reduced to 7 (seven) samples of the advertisements which contain “Preventing” and “Recovering”.There are 126 signs in total. The symbolic sign is mostly used in all advertisements.Every icon could be an index, and a symbol also could be an index. Each sign found in the advertisement has certain message related to the topic of the advertisements. The texts in the advertisements support the images to strengthen the meanings of the advertisements.Based on the results of the study, two suggestions can be recommended. The nextwriters or researchers might use other versions of Bear Brand Sterilized Milk and they might analyze the data by using other semiotics theories, such as Peirce’s triadic model of sign, Saussure’s dyadic model of sign, theory of codes by Chandler, etc.